Theological and Social Significance of Waqūduhan-Nāsu in Tafsir al-Azhar and al-Misbah: A Study of QS. al-Tahrīm [66]: 6 in the Al-Adab al-Ijtimā‘ī Framework - Abrar Muslim; Sona Zainal Walad; Ikbal Sabarudin; Eris Munandar; Mida Hardianti; Yahya Adel Ibrahim (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2026)
Allah admonishes the believers in QS. al-Tahrīm [66]: 6 to protect themselves and their households from the Fire, which is fuelled by people and stones (waqūduhan-nāsu wal-ḥijārah). This research investigates the theological and societal importance of the notion of waqūduhan-nāsu as interpreted by Hamka in Tafsīr al-Azhar and Quraish Shihab in Tafsīr al-Mishbah, with its ramifications assessed via the lens of adab al-ijtimāʿī. The research additionally contrasts the methods by which the two mufassir amalgamate theological understanding with social morality in elucidating the Qur’anic admonition that humanity may serve as the kindling for Hell. Hamka interprets waqūduhan-nāsu as a symbol of spiritual decline, indicating the continual perpetration of misdeeds by individuals, akin to the lifeless and aimless nature of stones. Shihab, on the other hand, emphasises the intrinsic ethical state of humankind, contending that spiritual decay and a lack of divine consciousness are the root causes of this state. Despite their varying interpretive frameworks, both academics perceive the statement as a symbolic depiction of humanity's ethical deterioration and its apocalyptic ramifications. Furthermore, their interpretations of the theological-social aspect suggest that the divine admonition is intrinsically linked to ethical and social obligations, thereby compelling individuals to foster personal integrity, familial devotion, and collective duty. In this sense, waqūduhan-nāsu functions as a concept linking human conduct in this world, spiritual condition, and social ethics.